Johannes Climacus and the Leap to Faith - Venkataraman, Prabhu (Horizons, 2018)
My goal in this article is to explicate the perspective of Kierkegaard's pseudonymous author, Johannes Climacus, on the leap to faith, based on Climacus' presentation in Philosophical Crumbs. I will argue that for Climacus, during the moment in which this leap is a possibility, while God must bring to the individual both the truth and the condition for understanding it, the leap is a decision by the individual, an existential decision to believe. In attempting to understand Climacus, it is important to use his definition of faith-namely, that faith is a passion and that it is the condition for understanding the paradox of the Christian conception of the Incarnation (as opposed to a synonym for religiosity), because this allows us to understand why faith is not an act of will but is simultaneously a decision (because belief is a free expression of will).